2017
DOI: 10.3748/wjg.v23.i23.4270
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of right-lobe and left-lobe living-donor liver transplantations using small-for-size grafts

Abstract: AIMTo analyze the outcomes of living-donor liver transplantation (LDLT) using left-lobe (LL) or right-lobe (RL) small-for-size (SFS) grafts.METHODSProspectively collected data of adult patients who underwent LDLT at our hospital in the period from January 2003 to December 2013 were reviewed. The patients were divided into the RL-LDLT group and the LL-LDLT group. The two groups were compared in terms of short- and long-term outcomes, including incidence of postoperative complication, graft function, graft survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…No significant differences were seen when comparing left and right lobes for the energy ratios during the split machine perfusion model. This highlights the potential in the split technique, as we can hypothesize that both lobes will behave metabolically and physiologically in the same way (28). In essence, if each lobe has good function, we are therefore able to further increase the donor pool by utilizing what previously was one suboptimal liver allograft into two viable transplantable allografts (27,29,30).…”
Section: The Rationale Of Organ Preservation By Machine Perfusionmentioning
confidence: 90%
“…No significant differences were seen when comparing left and right lobes for the energy ratios during the split machine perfusion model. This highlights the potential in the split technique, as we can hypothesize that both lobes will behave metabolically and physiologically in the same way (28). In essence, if each lobe has good function, we are therefore able to further increase the donor pool by utilizing what previously was one suboptimal liver allograft into two viable transplantable allografts (27,29,30).…”
Section: The Rationale Of Organ Preservation By Machine Perfusionmentioning
confidence: 90%
“…Graft failure is reported to occur in up to 7.8%, 14.6% and 26.5% of LDLTs at 1, 3 and 5 years with more favourable outcomes demonstrated in non-hepatocellular carcinoma (HCC) diagnoses and Model for End-stage Liver Disease (MELD) scores less than 20 (12). Furthermore, a study by She and colleagues reported, in an analysis of 218 patients, significantly better 5-year graft survival rates in using right lobe LDLT, albeit comparable 5-year patient survival rates (54). These findings were contrasted by Olthoff and colleagues who in a large multicentre study of 963 LDLTs demonstrated similar graft survival rates in right and left lobe LDLTs with decreasing rates of graft failure associated with greater centre experience (55).…”
Section: Living Donor Lt (Ldlt)mentioning
confidence: 99%
“…Accordingly, the accepted arbitrary requirement for GRWR was reduced to 0.8%, and the GV/SLV value was 40%[ 11 , 12 ]. As many transplantation centers accumulated experience on small-for-size grafts for LDLT, grafts with a GRWR < 0.8% were used and reported to be as safe as those with a GRWR ≥ 0.8%[ 13 - 17 ]. After challenging the boundary of GRWR = 0.8%, the acceptable minimum GRWR has been continuously lowered.…”
Section: Small-for-size Grafts In Ldltmentioning
confidence: 99%